"Sustainable Diets for the Earth: A Life Cycle Recipe for Low-Carbon Construction" (International Journal of Food and Nutritional Sciences, 2021)
The construction industry is a significant contributor to global carbon emissions, primarily due to the extraction and processing of raw materials. This study evaluates the potential carbon reduction benefits of using recycled aggregates (RA) instead of virgin aggregates (VA) in green building construction. A comparative Life Cycle Assessment (LCA) was conducted, assessing embodied carbon emissions from cradle-to-gate for both aggregate types in concrete production. Results indicate that incorporating recycled aggregates can reduce embodied carbon by approximately 25% without compromising structural integrity. This research highlights the environmental advantages of RA usage and provides a decision-making framework for sustainable material selection in green construction projects.